The Impact of Noise Models on Capacity Performance of Distribution Broadband over Power Lines Networks. (25th February 2016) - Lazaropoulos, Athanasios G.
Abstract : This paper considers broadband potential of distribution Broadband over Power Lines (BPL) networks when different well-known noise models of the BPL literature are applied. The contribution of this paper is twofold. First, the seven most representative and used noise models of the BPL literature are synopsized in this paper. With reference to this set, the broadband performance of a great number of distribution BPL topologies either Overhead (OV) or Underground (UN), either Medium-Voltage (MV) or Low-Voltage (LV), is investigated in terms of suitable capacity metrics. Second, based on the proposed capacity metrics, a comparative capacity analysis is performed among various well-validated noise models. Through the careful study of its results, it is demonstrated that during capacity computations of distribution BPL networks, the flat Additive White Gaussian Noise (FL noise model) can be comfortably assumed as an efficient noise model either in 3–30 MHz or in 3–88 MHz frequency range since its capacity differences with the other well-proven noise models are negligible.